Pendekatan Organisasi Industri dan Struktur Perilaku Kinerja Industri di Indonesia - Moch Fabiyano Alief Auliansyah; Muhammad Yasin (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study explores the role of industrial organization and market structure behavior in enhancing industrial performance in Indonesia. The objective of this research is to understand how organizational strategies and market structures influence industrial behavior and performance within the context of Indonesian industries. The method applied in this study is qualitative analysis, examining case studies from several industries in Indonesia, as well as analyzing organizational structures, competitive strategies, and external factors affecting industrial performance. The findings indicate that market structure and organizational behavior play a significant role in determining the competitiveness and efficiency of industries. The implications of this research are crucial for policymakers, industry leaders, and researchers to develop strategies that promote industrial growth, sustainability, and improved economic performance.